2014
DOI: 10.1039/c3en00053b
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative assessment of inhalation exposure and deposited dose of aerosol from nanotechnology-based consumer sprays

Abstract: This study provides a quantitative assessment of inhalation exposure and deposited aerosol dose in the 14 nm to 20 μm particle size range based on the aerosol measurements conducted during realistic usage simulation of five nanotechnology-based and five regular spray products matching the nano-products by purpose of application. The products were also examined using transmission electron microscopy. In seven out of ten sprays, the highest inhalation exposure was observed for the coarse (2.5–10 μm) particles wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
21
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 43 publications
3
21
0
Order By: Relevance
“…Using the surface area lung burden dose metric, some regulators have derived toxicity criteria for ultrafine TiO 2 that are~10-fold lower than fine TiO 2 (Dankovic et al, 2007;NIOSH, 2011); however, it remains unclear whether surface area fully explains the potency differences between fine and ultrafine TiO 2 (Section 3.3). Moreover, environmental exposure to pure ultrafine particles has been questioned (Nazarenko et al, 2012a(Nazarenko et al, , 2014. Our proposed RfC for TiO 2 includes a 3-fold UF D to account for uncertainties with respect to exposure to potentially more potent forms of TiO 2 (e.g.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Using the surface area lung burden dose metric, some regulators have derived toxicity criteria for ultrafine TiO 2 that are~10-fold lower than fine TiO 2 (Dankovic et al, 2007;NIOSH, 2011); however, it remains unclear whether surface area fully explains the potency differences between fine and ultrafine TiO 2 (Section 3.3). Moreover, environmental exposure to pure ultrafine particles has been questioned (Nazarenko et al, 2012a(Nazarenko et al, , 2014. Our proposed RfC for TiO 2 includes a 3-fold UF D to account for uncertainties with respect to exposure to potentially more potent forms of TiO 2 (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…For example, one study with three different ultrafine TiO 2 samples reported that the median diameters were >100 nm in water and >2.5 mm in phosphate buffered saline (Warheit et al, 2007). Recent studies with marketed cosmetic and spray products containing nanomaterials (some including TiO 2 ), found that nanoparticles within the products tend to agglomerate, thereby lessening exposure to ultrafine material (Nazarenko et al, 2014(Nazarenko et al, , 2012a(Nazarenko et al, , 2012b. Moreover, these studies also predicted that the vast majority of product deposition occurred in the head airways as opposed to alveolar regions of the lung (Nazarenko et al, 2012a(Nazarenko et al, , 2014.…”
Section: Introductionmentioning
confidence: 97%
See 2 more Smart Citations
“…Therefore, comparison of both suspension and aerosol analysis has been conducted in several studies 14,[16][17][18][19]32 to complement the limitations because it can suggest how the size and particle concentrations change during the spray process by the spray nozzle type. 15 There is no single analytical method or instrument able to evaluate the properties of nanoparticles in a variety of media in the F I G U R E 6 Temporal variation in count median diameter before and after spraying environment, so it could be obtained using a combination of some methods to complement the disadvantages of each method (physical properties: microscopic analysis, light scattering, field-flow fractionation, X-ray diffraction and etc; chemical composition: ICP-MS, EDX with EM, and others).…”
Section: Discussionmentioning
confidence: 99%